Tax Revenues in Fragile and Conflict-Affected States : Why Are They Low and How Can We Raise Them? - Akitoby, Bernardin (IMF Working Papers; Working Paper ;, 2020)
Raising revenues has been a formidable challenge for fragile and conflict-affected states (FCS), a fact confirmed once again in the COVID-19 crisis. Nonetheless, achieving sizable gains in tax collection in fragile environments is not impossible. This paper-with empirical analyses and case studies-contributes to policy discussions on tax reform in such challenging environments. Our analyses show that many FCS achieved some recovery of tax revenues, even though they found it challenging to sustain the momentum beyond three years. We also find that changes in the quality of institutions (e.g., government effectiveness and control of corruption) are a key contributory factor to their tax performance (much more so than for non-FCS). Next, we look into the tax increase episodes of four countries (Liberia, Malawi, Nepal, and the Solomon Islands). Although each FCS is unique, their experiences suggest two lessons: (i) tax reforms can be pursued even with initially weak institutions; and (ii) strong political commitment is important to sustain reform efforts and realize long-lasting, sizable gains.